ASEAN Response to the COVID-19 in the Economic, Health, and Tourism Sector - Zakiyy, Muhammad Nuha; Santoso, Rio Abei; Alviano, Yehezkiel Pramaditya (Universitas Sebelas Maret, 2020)
ASEAN is a regional organization consisting of several countries in the Southeast Asia region. The aim of establishing ASEAN is to cooperate and create an atmosphere of peace in the Southeast Asian region. In 2020, the world will be shocked by a complicated problem, namely the COVID-19 pandemic. The author tries to see the impact caused by COVID-19 and the ASEAN response in dealing with the issues that occur. The author uses the literature study method by using several sources from websites, news portals, reports, press releases, and journals to assess these cases. From this research, we can see that each country's problem consists of health, economic, and tourism problems. ASEAN's response in facing this pandemic includes collaborating in determining policies, exchanging information on each country's situation, and using tourism destination websites to restore the state of tourism in ASEAN.